Species composition and distribution of microalgae in the Sukhodol River estuary (Ussury Bay, Peter the Great Bay) in autumn. 2. Epiphyton - Nickolay V. Kolpakov; Andrey A. Begun; Arthur V. Olkhovik (Известия ТИНРО, 2014)
Epiphyte microalgae from common macrophytes ( Zostera marina, Z. japonica, Ruppia maritima, Ulva prolifera, Gracilaria verrucosa, Cladophora glomerata, Phragmites australis ) were sampled in the Sukhodol estuary in September of 2012. In total, 46 taxa of diatoms are registered, 72 % of them belong to microphytobenthos. The most numerous are mesohaline species and species indifferent to salinity (in sum 71 %). Similarity between species composition of phytoplankton and epiphyton was 57.4 %, by Czekanowski-Sørensen index. Total number of the epiphyton diatoms varied from 12.9 · 103 to 2583.9 · 103 cells/g wet weight of basiphyte (on average 541.1 · 103 ± 111.9 · 103 cells/g), their biomass varied from 17.4 to 3099.0 mg/g (on average 595.0 ± 134.7 mg/g). The lowest epiphyton biomass was registered for U. prolifera (33.9 ± 11.7 mg/g) and the highest - for Z. marina (2790.6 ± 166.8 mg/g). Species composition of epiphyton is significantly different between three groups of macrophytes: 1 - seagrass of external estuary ( Z. marina ); 2 - seagrasses ( Z. japonica, R. maritima ), attached bottom macroalgae ( U. prolifera, C. glomerata, G. verrucosa ) and emergent vegetation ( Ph. australis ) of internal estuary; and 3 - drifting macroalgae ( C. glomerata ) of internal estuary. Thus, species structure of epiphyte communities changes between biotopes and between water layers in each biotope that is determined by salinity preferences of the most common epiphytes, on the one hand, and vertical distribution of macrophytes within the water column, on the other hand. Domination of such α -mesosaprobionts as Tabularia tabulata , Melosira lineata and M. moniliformis var. subglobosa indicates eutrophication of the Sukhodol estuary that presumably is maintained by terrigenous biogenic elements supply. The biogenic elements recycled and accumulated in bottom sediments are dispersed in the estuarine waters by tidal and wind-driven turbulence.